Analisis Implementasi Fungsi Diplomasi Batas Maritim Yang Dilaksanakan Oleh Pusat Hidro-Oseanografi TNI Angkatan Laut (PUSHIDROSAL) - Yoyok Triono; Bram Rusman Namin; Gurtom Fatianto (PT. ALHAFI BERKAH INDONESIA, 2024)
This study aims to analyze the implementation of maritime boundary diplomacy conducted by the Hydro-Oceanography Center of the Indonesian Navy (Pushidrosal). The background of this research relates to the importance of establishing clear maritime boundaries for Indonesia as the largest archipelagic country, in order to safeguard sovereignty and effectively manage marine resources. The method used in this study is qualitative research, involving data collection through direct observation, interviews with Pushidrosal officials and hydro-oceanography experts, as well as analysis of related documents. The results indicate that Pushidrosal plays a crucial role in gathering and analyzing data to support Indonesia's maritime boundary claims, despite facing challenges such as limited resources and conflicts with neighboring countries. Recommendations for enhancing the effectiveness of maritime boundary diplomacy include increasing investment in survey technology, strengthening collaboration with other agencies, and involving the community in education about maritime boundaries.